Superstore: Season 3 - Ferrera, America; Feldman, Ben; Mckinney, Mark; Ash, Lauren; Dunn, Colton; Bloom, Nichole; Santos, Nico ([United States] : Universal Pictures Home Entertainment, 2018)
Attention all shoppers! Amy, Jonah, and the rest of the Cloud 9 employees are back for more retail adventures. Last season's whirlwind finale saw the aisles of Cloud 9 rocked by a massive tornado, leaving the fate of the store and the staff members hanging in the balance. The team must tackle getting back to the day-to-day grind while faced with attempted robberies, dead bodies on Halloween, and even an unexpected pregnancy.
09/04/2018
new dvd 2023 fall.
America Ferrera, Ben Feldman, Mark Mckinney, Lauren Ash, Colton Dunn, Nichole Bloom, Nico Santos.
MWT rating: NR.
DVD.
English audio.
Keywords: Television series